2018
DOI: 10.1038/s41558-018-0176-z
|View full text |Cite
|
Sign up to set email alerts
|

The ability of societies to adapt to twenty-first-century sea-level rise

Abstract: Against the background of potentially substantial sea-level rise, one important question is to what extent are coastal societies able to adapt? This question is often answered in the negative by referring to sinking islands and submerged megacities. Although these risks are real, the picture is incomplete because it lacks consideration of adaptation. This Perspective explores societies' abilities to adapt to twenty-first-century sea-level rise by integrating perspectives from coastal engineering, economics, fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
146
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 207 publications
(149 citation statements)
references
References 71 publications
1
146
0
2
Order By: Relevance
“…Previous studies have demonstrated that future climate change could result in extensive loss of coastal wetlands due to sea-level rise (Hinkel et al, 2018;Schuerch et al, 2018;Spencer et al, 2016).…”
Section: Potential Distributions Under Current and Future Climate Smentioning
confidence: 99%
“…Previous studies have demonstrated that future climate change could result in extensive loss of coastal wetlands due to sea-level rise (Hinkel et al, 2018;Schuerch et al, 2018;Spencer et al, 2016).…”
Section: Potential Distributions Under Current and Future Climate Smentioning
confidence: 99%
“…However, substantial uncertainty remains regarding which areas will experience retreat and how it will occur. Studies of economically robust coastal adaptation suggest that retreat will take place in lower-income, more rural areas (6,7), but case studies within the United States have primarily documented retreat in urban areas [e.g., (8)(9)(10)(11)], raising questions about whether predicted patterns of rural retreat will hold true within or across nations. Existing retreat experiences may also offer strategies relevant across international contexts and lessons about revisions needed to meet future demands.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Cinner et al (2018) proposed a framework to depict adaptive capacity of coastal communities across five domains: the assets that people can draw upon in times of need; the flexibility to change strategies; the ability to organize and act collectively; the ability to learn to recognize and respond to change; and the agency to determine whether to change or not. Hinkel et al (2018) explored societies' abilities to adapt to sea level rise by integrating perspectives from coastal engineering, economics, finance and social sciences. In addition, many case studies have been conducted to quantify to what extent human society is able to adapt to climate stresses, and adaptation capacity was generally defined and described from different perspectives and dimensions.…”
Section: Introductionmentioning
confidence: 99%